2021
DOI: 10.3390/nano11040898
|View full text |Cite
|
Sign up to set email alerts
|

Structuring of ZnTiO3/TiO2 Adsorbents for the Removal of Methylene Blue, Using Zeolite Precursor Clays as Natural Additives

Abstract: Adsorption is an effective method of removing harmful pollutants from air and water. In the present study, zeolites prepared by sol-gel method from two Ecuadorian clays were combined with precursor clays and the ZnTiO3/TiO2 semiconductor for adsorbing methylene blue (MB) as a water contaminant. The synthesized compounds were characterized using powder X-ray diffraction, X-ray fluorescence, scanning electron microscopy, energy dispersive X-ray, and surface area measurement. These compounds were combined to form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 104 publications
(111 reference statements)
0
19
0
Order By: Relevance
“…In a previous experimental paper, we reported the synthesis and characterization of the ZnTiO 3 /TiO 2 nanocomposite. This heterostructure was indexed to a hexagonal phase with space group R-3(148) for ZnTiO 3 and a tetragonal phase with space group I4 1 /amd(141) for TiO 2 (anatase) [39,40]. In these studies, we also reported the ability of ZnTiO 3/ TiO 2 to remove the methylene blue (MB) dye in aqueous systems, and it was contrasted with the results obtained for pure TiO 2 (anatase).…”
Section: Introductionmentioning
confidence: 99%
“…In a previous experimental paper, we reported the synthesis and characterization of the ZnTiO 3 /TiO 2 nanocomposite. This heterostructure was indexed to a hexagonal phase with space group R-3(148) for ZnTiO 3 and a tetragonal phase with space group I4 1 /amd(141) for TiO 2 (anatase) [39,40]. In these studies, we also reported the ability of ZnTiO 3/ TiO 2 to remove the methylene blue (MB) dye in aqueous systems, and it was contrasted with the results obtained for pure TiO 2 (anatase).…”
Section: Introductionmentioning
confidence: 99%
“…The relatively high surface area of the DE-immobilized ZTO/La nanocomposite could be a promising material for adsorption and photocatalysis, as well as for other applications. In fact, preliminary studies on the adsorption capacity and photocatalytic activity of the ZTO compound showed promising results for methylene blue (MB) removal in aqueous systems under irradiation with ultraviolet light [ 83 , 90 ]. Although the powdered materials usually have a higher SSA, in this study, the extrudates were chosen to adsorb MB due to their appropriate mechanical and chemical stability, which facilitated their recovery at the end of the process and their reuse after several cycles.…”
Section: Discussionmentioning
confidence: 99%
“…The ZnTiO 3 /TiO 2 (ZTO) and ZnTiO 3 /TiO 2 /La (ZTO/La) nanocomposites were synthesized following a modified sol-gel method described in previous studies [ 83 , 90 ]. To obtain the ZTO nanocomposite, a quantity of titanium (IV) isopropoxide (TiPO) in isopropyl alcohol (iPrOH) (70 v / v %) was dispersed at room temperature.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations